Description of a new species, nymphs of two known species and a new record of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Brazil - Raimundi, Erikcsen Augusto; Domínguez, Eduardo; Salles, Frederico Falcão (Zootaxa, 2021)
Miroculis is one of the most diversified Neotropical genera of Leptophlebiidae in South America with 26 species currently known. In this work we describe a new species of Miroculis based on imagos from Amazonas, and the unknown nymphs of Miroculis (Miroculis) caparaoensis and Miroculis (Ommaethus) misionensis, both associated with imagos. In addition, Miroculis (Ommaethus) misionensis is recorded for the first time from Brazil.